ANALISIS URGENSI DAN STRATEGI PELAYANAN PUBLIK DI KECAMATAN KWANDANG - Steven Alim, Mohamad; Hakeu, Febrianto; Saleh, Aulia; Jabar, Fidyawati (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2025)
This study aims to analyze the public service strategies implemented in the Kwandang District, with a focus on effectiveness, efficiency, and community satisfaction. Metode penelitian yang digunakan adalah metode deskriptif dengan pendekatan kualitatif. The results of the study show that digitization of services, humanist approach by apparatus, and coordination between institutions are the main strategies implemented. However, obstacles such as limited infrastructure, especially in remote areas, and low digital literacy among the community are still significant challenges. To overcome this, the Kwandang District government has made efforts such as training for officials and the community and increasing collaboration with the private sector to improve technological infrastructure. In conclusion, the success of the public service strategy in Kwandang District is highly dependent on improving infrastructure, human resource competence, and active community participation in utilizing digital-based services. Innovation in public services is important in realizing inclusive and efficient services in this region.